2020
DOI: 10.3390/cancers12040996
|View full text |Cite
|
Sign up to set email alerts
|

Pickled Vegetable and Salted Fish Intake and the Risk of Gastric Cancer: Two Prospective Cohort Studies and a Meta-Analysis

Abstract: An increased risk of gastric cancer for pickled vegetable and salted fish intake has been suggested, yet the lack of a dose-response association warrants a quantitative analysis. We conducted a meta-analysis, combining results from our analysis of two large Korean cohort studies and those from previous prospective cohort studies. We investigated the association of pickled vegetable and salted fish intake with gastric cancer in the Korean Genome Epidemiology Study and the Korean Multi-center Cancer Cohort Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…Some studies showed that biological and environmental factors, helicobacter pylori infection, excessive alcohol consumption, and smoking, can upregulate ADAM17 expression [ 39 , 40 , 41 , 42 , 43 ]. Helicobacter pylori infection may increase the incidence of gastric cancer and can increase the expression of ADAM17 in AGS gastric epithelial cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that biological and environmental factors, helicobacter pylori infection, excessive alcohol consumption, and smoking, can upregulate ADAM17 expression [ 39 , 40 , 41 , 42 , 43 ]. Helicobacter pylori infection may increase the incidence of gastric cancer and can increase the expression of ADAM17 in AGS gastric epithelial cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that pickled vegetables intake increases the risk of gastric cancer, 3,6,7,19 but its molecular mechanism in gastric carcinogenesis remains unclear. Metabolomics is now moving beyond biomarkers and towards mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Pickled vegetables were made with high concentrations of sodium chloride, which has been reported to induce mucosa and epithelial damage and produce chemical carcinogens-sodium nitrates and nitrites. 6 We speculate that long-term intake of pickled vegetables might affect the activity of metabolic enzymes in the folate metabolism pathway, which affected BH4 levels and BH4:BH2 ratio and perturbs the folate metabolism pathway, resulting in increased production of peroxynitrite and weakened T cell responses, which ultimately leads to tumor cell proliferation and immune escape. Then tumor cells are in a state of rapid proliferation and differentiation causing nucleotide synthesis and metabolism to be upregulated significantly.…”
Section: Dovepressmentioning
confidence: 94%
See 2 more Smart Citations